2010
DOI: 10.1177/0018726710378383
|View full text |Cite
|
Sign up to set email alerts
|

Emotional politics in cleaning work: The case of Israel

Abstract: Emotional politics instil insecurity and doubt in working-class individuals. Researchers examining social degradation through (bad) employment or other stigma have demonstrated the exclusionary impact of this process. Some suggest that individuals respond to such emotional politics and other types of exclusion by identity-management strategies aiming at a sense of worth, whereas others have found self-isolation to dominate. Here we analyse the emotional politics emerging from women's responses to exclusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Their education and socialization prevents them from developing ambitions and vision. They are trained to be at home, to live in it and its immediate surroundings (Abu-Rabia-Queder and Weiner-Levy 2010; Benjamin et al 2010), in a kind of gender contract that preserves the stability of the family (Sa'ar 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Their education and socialization prevents them from developing ambitions and vision. They are trained to be at home, to live in it and its immediate surroundings (Abu-Rabia-Queder and Weiner-Levy 2010; Benjamin et al 2010), in a kind of gender contract that preserves the stability of the family (Sa'ar 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have explored the impact of social class on a variety of topics such as work attitudes and interactions (e.g., Benjamin, Bernstein, & Motzafi-Haller, 2011;Gray & KishGephart, 2013;Judge & Hurst, 2007), careers and career mobility (e.g., Audretsch et al, 2013;McLeod, O'Donohoe, & Townley, 2009;Snipp, 1985), work life balance (e.g., Lautsch & Scully, 2007), job performance (e.g., Johnson, Messe, & Crano, 1984), and perceptions of risk (e.g., Cooper, 2008). This research often found distinctions between individuals of varying social class.…”
Section: Social Classmentioning
confidence: 99%
“…Cross-class interactions, which are described as interactions between individuals of differing social class (Ridgeway & Fiske, 2012), have been found to be frustrating (Benjamin et al, 2011;Gray & Kish-Gephart, 2013) as these interactions frequently highlight a lack of shared experiences.…”
Section: Hiring Manager and Applicant Social Class Similaritymentioning
confidence: 99%
“…Studies have investigated dirty workers' responses to the shame and humiliation that doing their dirty work might bring (for example , Holmqvist 2009;Benjamin, Bernstein, and Motzafi-Haller 2010). Workers cleaning public lavatories in Israel were found to have varying ethnic, historical and social experiences that negatively impacted their experiences of family, community and work (Benjamin, Bernstein, and Motzafi-Haller 2010).…”
Section: Dirty Work and Dirty Workersmentioning
confidence: 99%
“…Workers cleaning public lavatories in Israel were found to have varying ethnic, historical and social experiences that negatively impacted their experiences of family, community and work (Benjamin, Bernstein, and Motzafi-Haller 2010). Swedish workers found themselves being 'made' into disabled workers (regardless of disability or impairment) due to their work being considered 'suitable' for disabled people, yet too undignified, disgusting, dirty or unpleasant for able-bodied workers (Holmqvist 2009, 875-877).…”
Section: Dirty Work and Dirty Workersmentioning
confidence: 99%